Enhancing soil health and crop yields through water-fertilizer coupling technology - Xing, Yingying; Zhang, Xiangzhu; Wang, Xiukang (Frontiers in Sustainable Food Systems, 2024)
Water-fertilizer coupling technology has emerged as a pivotal strategy in modern agriculture, recognized for its potential to enhance soil environmental quality, promote crop growth, and ensure sustainable resource utilization. With increasing global food demands and environmental concerns, optimizing agricultural practices is essential for achieving food security and ecological balance. This review aims to systematically review the direct impacts of water-fertilizer coupling on the physical, chemical, and biological properties of soil, while elucidating the underlying mechanisms that drive crop responses. Additionally, it evaluates the optimization of water-fertilizer coupling technology and its associated environmental benefits. The findings indicate that water-fertilizer coupling significantly improves soil structural stability, enhances microbial diversity, and increases soil enzyme activities. An appropriate water-fertilizer ratio markedly boosts soil microbial biomass carbon and nitrogen content, facilitating nutrient mineralization and accelerating the decomposition of organic matter. The implementation of intelligent water-fertilizer management systems has shown to enhance water use efficiency and reduce fertilizer loss rates, thereby minimizing the environmental footprint of agricultural production.The optimization of water-fertilizer coupling is crucial for improving soil health, crop yields, and resource efficiency. This technology not only supports sustainable agricultural practices but also contributes to national food security and rural revitalization efforts. Future research should focus on the interaction mechanisms among crops, soil, water, and fertilizer. It is essential to strengthen the development of water-fertilizer coupling regulation models and decision support systems to guide agricultural production practices effectively. Policymakers are encouraged to promote the adoption of integrated water-fertilizer management strategies to foster sustainable agricultural development and enhance environmental resilience. This review underscores the importance of advancing water-fertilizer coupling technology as a means to achieve sustainable agricultural productivity while safeguarding ecological integrity, aligning with the principles of socialism with Chinese characteristics.